Competence and Motivation and Workplace Performance - Wahyudi, Wahyudi; Hayati, Neneng (SEIKO : Journal of Management & Business, 2023)
PT. Jasindo Insurance Selindo Indonesia is the subject of this study, which intends to investigate and analyse the impact of motivation and competence on performance. Employees of PT. Asuransi Jasindo Selindo, or 122 people in all, will constitute the population studied. The sample formula put forward by Slovin and Husein Umar is used by the authors to calculate the sample size. The sample size for this study is 54 individuals, according to this formula. The design of this study was based on survey research as the primary method of data collecting. Quantitative and qualitative data are the two categories of data used in this study. Multiple linear regression analysis and descriptive analysis will be performed on the acquired data. Keywoard: Staff performance, competence and motivation